Using Music to Help Emotionally Disturbed Children Develop Social Skills in the Classroom - Balmages, Lisa (My University, 2010)
This study was conducted to determine if music could be used to help emotionally disturbed children develop better social skills in the classroom. For this study, music from the Tuned in to Learning Volume 1, Social Skills & Pragmatics Curriculum was used. In addition, supplementary material from Socially Smart: Teaching Social Skills Through Scripts and Songs was used during the intervention period. Social behaviors that were assessed include the following behavior categories: off‐task behavior, impulse control, refusal to participate, and not keeping personal space. The hypothesis was not supported because students overall still showed poor social skills after the intervention was completed.
To see paper in its entirety contact archives@goucher.edu or call (410)337-6075.
Keywords: Education -- Research papers (Graduate); Music in education; Adjustment disorders in children; Social skills -- Study and teaching